From Intern to Industry Professional: How Work Experience and Satisfaction Influence Career Intentions in the Hotel Sector - Dina Zikrah; Ilham; Haru Hasnel; Feri Ferdian (Journal of Business on Hospitality and Tourism, 2025)
The hospitality industry faces persistent challenges in talent retention, particularly among new graduates. This study investigates how the nature of work and internship satisfaction jointly influence future career intentions among hotel management students in Indonesia. Using a quantitative, causal-comparative design, data were collected from 115 students at Universitas Negeri Padang who had completed internships in the hotel sector. Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed to test a mediation model. Results indicate that (1) the nature of work positively affects career intentions (β = 0.531, p < 0.001); (2) internship satisfaction also has a significant positive effect (β = 0.571, p < 0.001); and (3) internship satisfaction fully mediates the relationship between work nature and career choice (indirect effect = 0.094, p = 0.080). Contrary to expectations, the nature of work did not significantly predict internship satisfaction (p = 0.080), suggesting that students’ career decisions are shaped more by their overall satisfaction with the internship experience than by specific job characteristics. These findings underscore the strategic importance of designing meaningful, supportive internship programs to cultivate long-term industry commitment.